A Companion to Death, Burial, and Remembrance in Late Medieval and Early Modern Europe c.1300-1700
1 online resource.
Keywords: This companion volume seeks to trace the development of ideas relating to death, burial, and the remembrance of the dead in Europe from ca.1300-1700. Examining attitudes to death from a range of disciplinary perspectives, it synthesises current trends in scholarship, challenging the old view that the Black Death and the Protestant Reformations fundamentally altered ideas about death. Instead, it shows how people prepared for death; how death and dying was imagined in art and literature; and how practices and beliefs appeared, disappeared, changed, or strengthen over time as different regions and communities reacted to the changing world around them. Overall, it serves as an indispensable introduction to the subject of death, burial, and commemoration in thirteenth to eighteenth century Europe.